Build and Code Creative Robots with LEGO BOOST Unleash Your Creativity and Imagination by Building Exciting Robotics Projects. - Shah, Ashwin (Packt Publishing, Limited, 2021)
Further reading -- Chapter 7: Building a Helicopter -- Technical requirements -- Building a helicopter -- Let's code the robot to perform various tasks -- Activity #1 -- Activity #2 -- Activity #3 -- Activity #4 -- Activity #5 -- Time for a challenge -- Summary -- Further reading -- Chapter 8: Building R2-D2 -- Technical requirements -- Building the R2-D2 robot -- Let's code the robot to move on a specific path -- Activity -- Time for a challenge -- Summary -- Further reading -- Chapter 9: Building an Automatic Entrance Door -- Technical requirements.